Long-term cost and efficacy analysis of latanoprost versus timolol in glaucoma patients in Germany - Thelen, Ulrich (International Journal of Ophthalmology Press, 2013)
AIM: To evaluate 5-year effectiveness and cost between latanoprost or timolol monotherapy in a pilot trial. METHODS: A retrospective, multi-center trial performed at 6 sites in Germany of patients who had a diagnosis of primary open-angle or pigmentary glaucoma, in at least one eye, initiated on monotherapy with latanoprost or timolol maleate. Qualified consecutive charts were reviewed in which 5-year efficacy, safety and cost data was abstracted. RESULTS: Seventy-seoen latanoprost and 49 timolol patients were included, at the final visit no difference existed between the two groups in disc parameters including: rim area, rim area/disc area ratio, cup volume or vertical cup/disc ratio (P>0.05). There was no difference in intraocular pressure (IOP) between the initial latanoprost (17.4±2.6) and timolol (16.3±2.8mmHg) groups. There was less change in medicines over the follow-up period (0.1 vs 0.8) and fewer medications at the final visit (1.2 vs 1.8) with latanoprost compared to timolol. No patient treated with latanoprost discontinued therapy during follow-up, while 12% discontinued timolol mostly due to inadequate IOP control. Cost/year was less with initial timolol ($458±236) as compared to latanoprost ($552±202). CONCLUSION: Patients begun on latanoprost or timolol and followed over 5 years may have similar clinical outcomes. However, timolol patients may require more medicines and medicine changes to control IOP for long-term, but at a lower cost.